2013
DOI: 10.1177/1078155213498630
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to anti-cancer drugs: A review of effects of new technology

Abstract: Because anti-cancer drugs are non-selective, they affect both cancerous and non-cancerous cells. Being carcinogenic and mutagenic, many anticancer drugs therefore present a major health risk to healthcare staff working with them. This paper reviews the means by which exposure to anti-cancer drugs in the workplace may be monitored, assessed and reduced. Both biological monitoring, using non-selective methods or compound-selective methods, and environmental monitoring have provided information on the nature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…Moreover, a potentially less strict application of safety recommendations or hygiene strategies, or lack of experience in AD preparation due to smaller preparation numbers may also be reasons for higher contamination incidents. As expected, results show that BSCs and isolators were frequently contaminated, which has also been shown in other studies [12,19,22,[30][31][32][33][34], and also the waste disposal systems (e. g.; Pactosafe). At these locations, large quantities of drugs are handled and spillage is likely to happen.…”
Section: Overall Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, a potentially less strict application of safety recommendations or hygiene strategies, or lack of experience in AD preparation due to smaller preparation numbers may also be reasons for higher contamination incidents. As expected, results show that BSCs and isolators were frequently contaminated, which has also been shown in other studies [12,19,22,[30][31][32][33][34], and also the waste disposal systems (e. g.; Pactosafe). At these locations, large quantities of drugs are handled and spillage is likely to happen.…”
Section: Overall Resultssupporting
confidence: 88%
“…This is most likely related to the increased awareness of the health hazard of occupational exposure to ADs and to the implementation of international and national guidelines. Levels seem to decrease since the introduction of technical improvements such as CSTDs [30], standardized working and cleaning strategies and environmental contamination controls on practice quality [21,27,31,32,49,50]. But it is also substantially dependent from the sufficient adherence to recommended practices, which are -as even shown in recent studies -often insufficiently followed [47,51,52].…”
Section: Long-term Monitoring Of Surface Contaminationmentioning
confidence: 99%
“…These drugs are less likely to be positive for a surface wipe sample. The hospital also used CSTDs to prepare and administer chemotherapy, which studies have shown can reduce surface contamination [Sessink and Bos 1999;Nygren et al 2002;NIOSH 2004;Harrison et al 2006;Nyman et al 2007;Yoshida et al 2009;Sessink et al 2010;Vyas 2013]. Another possible reason most of the samples did not detect any drug is that the level of hazardous drugs on surfaces varies over time.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] In addition, many CSTDs are needle-free and their implementation would therefore reduce the risk of needlestick injuries. 26 However, the added costs of CSTDs might be a barrier to their adoption. Another engineering control that should be widely implemented is use of a ventilated hood, such as a biological safety cabinet (BSC), when mixing drugs, to prevent possible exposure via inhalation.…”
Section: Discussionmentioning
confidence: 99%